Implementation of an accelerated mobilization protocol following primary total hip arthroplasty: impact on length of stay and disposition - Wellman, Samuel S. (Current Science Inc., 2011)
With improvements in surgical techniques, implant design, and patient caremaps, surgeons have sought to accelerate early rehabilitation after total hip arthroplasty. Many authors have reported results of fundamentally similar protocols to achieve this end. These protocols focus on multi-modal pain management, early therapy, tissue-preserving surgical technique, and careful blood management. We present the implementation and results of such a protocol involving a different surgical approach, and highlight the published literature on this topic.